Instagram Photo Sharing and Its Relationships With Social Connectedness, Loneliness, and Well-Being. (June 2022) - Maclean, Julie; Al-Saggaf, Yeslam; Hogg, Rachel
Photo sharing is one of the most popular online social media activities and has been associated with changes in mental health. Research investigating the effect of sharing photos on a social media user's social connectedness, loneliness, and well-being has generated conflicting results. This study analyzed the effect of Instagram photo sharing on the relationships among social connectedness, loneliness, and well-being. The study focused on photos sharing separate to viewing photos to understand the specific effect of photo sharing. The research measured how those with transient and chronic levels of loneliness respond differently to photo sharing, which has not been previously considered. Well-being and loneliness are conceptualized as dependent variables that have a relationship with social connectedness as an independent variable, which is moderated by the number of photos shared. Results from an online survey of 373 participants found Instagram photo sharing does significantly moderate relationships among social connectedness, loneliness, and well-being. Highest levels of photo sharing were found to have the largest moderating effect. Levels of well-being decreased as social connectedness and photo sharing increased. Differences were found for types of loneliness where photo sharing was most beneficial at low levels of social connectedness for transient loneliness. In contrast, for those experiencing chronic trait loneliness, high levels of photo sharing were associated with highest levels of loneliness when social connectedness was high. One obvious implication for social media and policy may lie in education for users and technology enhancement for optimal photo sharing levels that minimize loneliness and maximize well-being.